Applications of cesium in the perovskite solar cells *Project supported by the 973 Program of China (No. 2015CB932203), the National Natural Science Foundation of China (Nos. 61377025, 91433203), and the Young 1000 Talents Global Recruitment Program of China. (January 2017) - Ye, Fengjun; Yang, Wenqiang; Luo, Deying; Zhu, Rui; Gong, Qihuang
Abstract: Perovskite solar cells have experienced an unprecedented rapid development in the power conversion efficiency (PCE) during the past 7 years, and the record PCE has been already comparable to the traditional polycrystalline silicon solar cells. Presently, it is more urgent to address the challenge on device stability for the future commercial application. Recently, the inorganic cesium lead halide perovskite has been intensively studied as one of the alternative candidates to improve device stability through controlling the phase transition. The cesium (Cs)-doped perovskites show more superior stability comparing with organic methylammonium (MA) lead halide perovskite or formamidinium (FA) lead halide perovskite. Here, recent progress of the inorganic cesium application in organic–inorganic perovskite solar cells (PSCs) is highlighted from the viewpoints of the device efficiency and the device stability.